2018
DOI: 10.1177/0095327x17752900
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Lapses and the Military Profession

Abstract: In a recent issue of this journal, we published an article titled “Fault Lines of the American Military Profession”. Donald S. Travis subsequently wrote a Dipustatio Sine Fine rejoinder that raised a number of criticisms of our piece and suggested several ways forward. For our part, we detect three serious problems in Travis’s analysis and offer a single syncretic response. Our solution builds on the insights of Travis’s critique while avoiding the pitfalls of his specific line of reasoning. We conclude by urg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The seminal critique in this line of research comes from Janowitz (1960) who showed that Huntington’s perspective is not robust enough to deal with a variety of managerial and technical aspects of the profession and requires some acknowledgment of politics as a central part of war-making. More recently, Crosbie and Kleykamp (2018a) discuss how scholars model the relationship between civil–military relations and military professionalism shapes their research in important ways.…”
Section: Huntington and The Normal Schoolmentioning
confidence: 99%
“…The seminal critique in this line of research comes from Janowitz (1960) who showed that Huntington’s perspective is not robust enough to deal with a variety of managerial and technical aspects of the profession and requires some acknowledgment of politics as a central part of war-making. More recently, Crosbie and Kleykamp (2018a) discuss how scholars model the relationship between civil–military relations and military professionalism shapes their research in important ways.…”
Section: Huntington and The Normal Schoolmentioning
confidence: 99%
“…11 Measures relating to range and variability of advice across elite military offices, the uncertainty surrounding military projections, and presence (or absence) of scientific support for military advice were proposed, however, in the politically charged, hothouse environment of 2006–2007. Moreover, the implications emerged from a civilian supremacist theory of the case, laying blame for the collapse of constructive civil–military dialogue at the feet of the military and probing what might be done by senior officers, even in the face of cantankerous future secretaries of defense, to repair relations for improved national security decision-making (Coletta, 2007; Crosbie & Kleykamp, 2017, 2018).…”
Section: Civilian Supremacists Versus Principled Patriotsmentioning
confidence: 99%
“… 3. Signs of resurging interest in Janowitz include the reissue of The Professional Soldier , several recent conference panels dedicated to Janowitz’s life and work, and the Army Research Institute’s funding of Crosbie’s ongoing replication of The Professional Soldier . See also Travis (2017, 2018) and Crosbie and Kleykamp (2017, 2018). …”
mentioning
confidence: 99%
“…Recently, military scandals, as with scandals more generally, are attracting increased scholarly attention (Baugut, 2017; Crosbie, 2015; Crosbie & Sass, 2017; Habiba, 2017; Haller et al, 2018; Tumber & Waisbord, 2019; Wadham, 2016). Spurred by both growing scholarship on media–military relations (Corner & Parry, 2017; Hoskins & O’Loughlin, 2015; Maltby, 2012a, 2012b) and major episodes (Crosbie & Kleykamp, 2018) such as the HMS Vigilant (Wootson, 2017), “Fat Leonard” (Back, 2019), “Marines United” (Chappell, 2017), and the “Skype” scandal in Australia (Habiba, 2017; Wadham, 2016), studies of military scandals have raised both ontological and epistemological questions: What are military scandals? How can they be studied?…”
Section: The Military Scandal As a Phenomenon Of Interdisciplinary Inmentioning
confidence: 99%